Study of Genetic Polymorphism in the Mitochondrial DNA of the Mediterranean Fruit Fly Ceratitis Capitata (Wiedemann, 1824) (Diptera:Tephritidae)Using the Method of PCR-RFLP in Three Governorates in the Middle Region of Iraq. - Jawad, M.M.; Al-Asady, H.S.; Hussein, I.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Genetic polymorphism in a fragment of NADH (ND4),400bp long from the Mitochondrial DNA (mtDNA) of Mediterranean fruit fly ceratitis capitata (Wiedemann, 1824) using PCR-RFLP method with the restriction enzyme EcoRV in samples collected from three governorates in the middle of Iraq. The purposes of this study is to establish database, discover the introduction source as well as studying the genetic diversity for this economic pest in Iraq. The results show that there is a genetic polymorphism of the studied gene fragment among Kut governorate as compaired with the other studied samples according to digestion results of the restriction enzyme EcoRV.